2023
DOI: 10.1002/mog2.23
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virotherapy using neural stem cells as a novel treatment option for glioblastoma multiforme

Abstract: The most deadly and aggressive form of brain cancer is called a glioblastoma multiforme. Following diagnosis, the median duration of survival is only 14 months. It is imperative to develop cutting‐edge therapeutic options because the results of conventional treatments are so poor. Replication‐competent oncolytic viruses and replication‐deficient viral vectors can be used to treat malignant tumors, an idea that has been around for more than a century. Cancer cells can be eliminated by any class. Oncolytic virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 204 publications
0
2
0
Order By: Relevance
“…Experiments have shown that the system‐injected oncolytic reovirus can be carried by immune cells to cross the BBB 177 . This provides new ideas for OVs to cross the blood‐brain by being loaded on brain‐targeted cells, such as neural and mesenchymal stem cells 247 . Currently, BM‐hMSCs‐DNX‐2401 (NCT03896568) and NSCs‐CRAd‐S‐pk7 (NCT03072134) are validating the feasibility of this strategy.…”
Section: Challenges In Oncolytic Virus Treating For Gliomamentioning
confidence: 97%
See 1 more Smart Citation
“…Experiments have shown that the system‐injected oncolytic reovirus can be carried by immune cells to cross the BBB 177 . This provides new ideas for OVs to cross the blood‐brain by being loaded on brain‐targeted cells, such as neural and mesenchymal stem cells 247 . Currently, BM‐hMSCs‐DNX‐2401 (NCT03896568) and NSCs‐CRAd‐S‐pk7 (NCT03072134) are validating the feasibility of this strategy.…”
Section: Challenges In Oncolytic Virus Treating For Gliomamentioning
confidence: 97%
“…177 This provides new ideas for OVs to cross the blood-brain by being loaded on brain-targeted cells, such as neural and mesenchymal stem cells. 247 Currently, BM-hMSCs-DNX-2401 (NCT03896568) and NSCs-CRAd-S-pk7 (NCT03072134) are validating the feasibility of this strategy. Endovascular selective intra-arterial (ESIA) infusion can deliver drugs into glioma tumors when injected systemically, enhancing drug delivery and targeting tumor vasculature selectively.…”
Section: Delivery Of Ovsmentioning
confidence: 98%